Qur’anic Education on Financial Intelligence - Muh mustakim; Fitria Nur Farida (Yayasan Azhar Amanaa Yogyakarta, 2026)
This article examines the Quranic indications regarding financial intelligence from a Quranic Education perspective using a qualitative research method with a thematic interpretation approach (tafsīr al-mawḍū'ī). The research findings show that financial intelligence in the Qur'an is implied in the terms māl, which implies financial awareness, rizq (wealth mindset), infaq (financial allocation), dayn (responsible financing), tabżīr (financial self-control) and isrāf (moderate consumption). These findings confirm that financial intelligence from a Quranic Education perspective is not merely the ability to accumulate wealth, but also to manage it to realize ḥifẓ al-māl, as the primary objective of maqāṣid al-shari'ah. This study implies that financial intelligence from the perspective of Qur'anic education is an educational system that can shape financial behavior that integrates spirituality, morality, and managerial aspects. This concept can be the basis for curriculum development, family education, educational institution governance, Islamic financial literacy, and public policy. The main principle of this research finding suggests that financial intelligence from the perspective of Qur'anic education is not only oriented towards improving economic welfare, but also towards realizing trustworthy, just, sustainable wealth management, and in line with the objectives of maqāṣid al-sharī'ah, especially ḥifẓ al-māl.